The imprint of a symbiotic binary progenitor on the properties of Kepler's supernova remnant - Chiotellis, A; Schure, K; Vink, J (2012)
We present a model for the type Ia supernova remnant (SNR) of SN 1604, also known as Kepler's SNR. We find that its main features can be explained by a progenitor model of a symbiotic binary consisting of a white dwarf and an AGB donor star with an initial mass of 4-5 M ⊙. The slow, nitrogen-rich wind emanating from the donor star has partially been accreted by the white dwarf, but has also created a circumstellar bubble. On the basis of observational evidence, we assume that the system moves with a velocity of 250 km s -1. Owing to the spatial velocity, the interaction between the wind and the interstellar medium has resulted in the formation of a bow shock, which can explain the presence of a one-sided, nitrogen-rich shell. We present two-dimensional hydrodynamical simulations of both the shell formation and the SNR evolution. The SNR simulations show good agreement with the observed kinematic and morphological properties of Kepler's SNR. In particular, the model reproduces the observed expansion parameters (m = V/(R/t)) of m ≈ 0.35 in the north and m ≈ 0.6 in the south of Kepler's SNR. We discuss the variations among our hydrodynamical simulations in light of the observations, and show that part of the blast wave may have completely traversed through the one-sided shell. The simulations suggest a distance to Kepler's SNR of 6 kpc, or otherwise imply that SN 1604 was a sub-energetic type Ia explosion. Finally, we discuss the possible implications of our model for type Ia supernovae and their remnants in general. © 2012 ESO.